ANSH: Multimodal Neuroimaging Database Including MR Spectroscopic Data From Each Continent to Advance Alzheimer’s Disease Research - Mandal, Pravat K.; Sandal, Kanika; Shukla, Deepika; Tripathi, Manjari; Singh, Kuldeep; Roy, Saurav (Frontiers in Neuroinformatics, 2020)
Alzheimer’s disease (AD) is a devastating neurodegenerative disorder that affects cognitive abilities, activities in daily living and no disease modifying treatment is available till date. The amyloid beta theory for AD has prevailed for more than two decades and now, another alternative hypothesis like oxidative stress theory is getting consideration. AD is multifactorial disease and various brain imaging modalities have a profound role to provide critical information to the global researchers for the extraction of various features to identify the causal molecular process for AD. An imaging-based database, initiative started at University of Washington, has emerged as a key player in AD research. Other centers or university driven initiatives have taken lead afterwards and subsequently major datasets were released for the researchers. These databases are centered in United States of America and Canada comprising primarily of structural and functional Magnetic Resonance Imaging, Positron Emission Tomography, and behavioral data of healthy old and AD patients. All existing databases did not include neurochemical profile of AD patients. Previous studies have highlighted the usability of Magnetic Resonance Spectroscopy (MRS) in investigations related to neuronal marker, oxidative stress, and neurotransmitter modulation to identify early diagnostic biomarker of AD. This editorial is an initiative to bring forth the critical requirement of neuroimaging databases entailing the neurochemical profile along with other neuroimaging and behavioral information. We present a new framework to start this process for developing a multinuclear MRS based database along with structural, functional, and behavioral data from Indian subcontinent for AD research.